Matriarch recalls Dawson days (Raton Range Raton, New Mexico, 1984)
Newspaper Article on the 48th Anniversary of Frederico and Mariana Rivera and her marriage.
Master list item #: 34
File location is in the Raton File Cabinet
Keywords: Rivera, Federico; Rivera, Mariana; Local History; Biography; Life and Customs; Marriage; Celebration; Anniversary; Arranged marriage; Raton, New Mexico; Ocate, New Mexico; Trinidad, Colorado; Dawson, New Mexico